Blinded From the Truth? Perceptions of Racial Discrimination During COVID-19 - Mitrovic, Igor (University of Waterloo, 2021)
Despite current efforts to reduce the occurrence of racial discrimination in North America, the recent Black Lives Matter movement suggests that the issue continues to exist. Given that prior research suggests a link between perceptions of discrimination and behaviours and attitudes that perpetuate discrimination, a correlational study was conducted with the purpose of examining whether a current social/global crisis, the COVID-19 pandemic, is associated with such perceptions, thus contributing to the continued existence of racial discrimination. It is predicted that heightened feelings of threat associated with the various repercussions of the COVID pandemic would be associated with heightened justification of the United States social system, and in turn negatively associated with perceptions of racial discrimination towards Black Americans. Furthermore, it is predicted that this indirect effect would be more pronounced in political conservatives than in liberals. An online survey study was conducted on 528 American participants to test these hypotheses. Initial hierarchical regression analyses indicated that COVID threat was not significantly associated with system justification, but that both COVID threat and system justification were significantly associated with perceived racial discrimination (although COVID threat was positively associated with perceived discrimination). Mediation analyses indicated that there was no significant indirect effect of COVID threat on perceived racial discrimination through system justification. Finally, although there were no significant moderated-mediation effects, there were significant interaction effects between COVID threat and political orientation on perceived discrimination, with a more pronounced effect in political conservatives than in liberals. The limitations and implications of the study are discussed.
Keywords: System Justification; Racial Discrimination; Perceptions; COVID-19